Fabrication and characterization of thin film solar cells using liquid dopant by spin coating method: article - Hussin @ Jaafar, Mohd Hafizuddin; Mohd Noor, Uzer (2014)
This report presents the fabrication and characterization of thin film solar cells using liquid dopant by spin coating method at different spin speed and annealing temperatures. Silicon is still the most widely used element for solar cell production, due to the improvement of physical properties of silicon structures. Thus the aims of the study are to fabricate and characterize the thin film solar cell using phosphorosilicafilm 3 x 1020 liquid dopant. Phosphorosilica doped p-type silicon thin films were successfully deposited by spin coating in the range of 2000 - 4000 rpm and by using annealing temperature range of 700⁰C - 900⁰C in 30 minutes diffusion. The characterized of the film that influence of various spins speed and annealing temperature consist of electrical and physical properties. The properties of thin films solar cell were characterized by using Solar Simulator (Bukoh Keiki CEP-2000) and Field Emission Scanning Electron Microscope (FESEM) to measure current-voltage (I-V), Voc, Isc and fill-factor (FF) to get the efficiency (ƞ) and for structure characterization.